.NET MAUI cross-platform application development leverage a first-class cross-platform UI framework to build native apps on multiple platforms - Ye, Roger (PACKT PUBLISHING LIMITED, 2023)
Build apps for Android, iOS, macOS, and Windows using Microsoft's .NET Multi-platform App UI and Blazor Key Features Get familiar with Microsoft's UI toolkit to build amazing interfaces for iOS, Android, Windows, and macOS Build a cross-platform password manager based on the famous Windows app, KeePass Explore .NET MAUI development and Hybrid app development using Blazor Book Description An evolution of Xamarin.Forms, .NET Multi-platform App UI (.NET MAUI) is a cross-platform framework for creating native mobile and desktop apps with C# and XAML. Using .NET MAUI, you can develop apps that'll run on Android, iOS, macOS, and Windows from a single shared code-base. This step-by-step guide provides a comprehensive introduction to those who are new to .NET MAUI that will have you up to speed with app development using .NET MAUI in no time. The book begins by showing you how to develop a cross-platform application using .NET MAUI and then helps you build an app throughout the chapters. You'll gain all the knowledge needed to create a cross-platform application for Android, iOS, the mac OS, and Windows from a single shared code-base using .NET MAUI. As you advance, you'll get to grips with the entire application development lifecycle, from design and implementation through to deployment to the app store through the development of a password manager app using KeePassLib. The concluding chapters will teach you how to integrate the latest frontend technology into your app through .NET MAUI Blazor. By the end of this book, you'll have learned how to develop your own cross-platform applications using .NET MAUI. What you will learn Discover the latest features of .NET 6 that can be used in mobile and desktop app development Find out how to build cross-platform apps with .NET MAUI and Blazor Implement device-specific features using .NET MAUI Essentials Integrate third-party libraries and add your own device-specific features Discover .NET class unit test using xUnit.net and Razor components unit test using bUnit Deploy apps in different app stores on mobile as well as desktop Who this book is for This book is an entry-level .NET MAUI book for mobile developers interested in cross-platform application development with working experience of the .NET Core framework, as well as fresh or junior engineers who've just begun their career in mobile app development. Native application developers (desktop) or Xamarin developers who want to migrate to .NET MAUI will also benefit from this book. Basic knowledge of modern object-oriented programming language, such as C#, Java or Kotlin, is assumed.